Accreditation of Experiences in Public and Private Tenders through Corporate Reorganizations - Enríquez Cuellar, Carlos (2022)
This article seeks to carry out an analysis regarding the application of Corporate Reorganizations as mechanisms to accredit the transfer of ownership of Experiences in Public and Private Tenders before the authority in charge of regulating said procedures in Peru (OSCE). In this way, we analyze the main regulatory pronouncements and technical opinions issued, as well as relevant accounting provisions that are applicable, complementing this with our legal analysis of regulatory provisions applicable to corporations, so that we can develop an optimal corporate planning suitable for this type of operations.